2017
DOI: 10.1016/j.celrep.2017.04.058
|View full text |Cite
|
Sign up to set email alerts
|

Absence of Specific Chlamydia trachomatis Inclusion Membrane Proteins Triggers Premature Inclusion Membrane Lysis and Host Cell Death

Abstract: Summary Chlamydia trachomatis is a human pathogen associated with significant morbidity worldwide. As obligate intracellular parasites, chlamydiae must survive within eukaryotic cells for sufficient time to complete their developmental cycle. To promote host cell survival, chlamydiae express poorly understood anti-apoptotic factors. Using recently developed genetic tools, we show that three inclusion membrane proteins (Incs) out of eleven examined are required for inclusion membrane stability and avoidance of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
117
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 89 publications
(134 citation statements)
references
References 68 publications
(91 reference statements)
7
117
0
Order By: Relevance
“…By targeted gene disruption of individual Inc proteins in Ctr , mutants of IncC, CT383, and CT229/CpoS exhibited a significant growth defect and premature inclusion lysis followed by host cell death. These results were further confirmed in mouse genital infection studies (Weber et al, ). Independent studies identified several Rab proteins as interaction partners of CT229/CpoS, and inhibition of host cell protein biosynthesis or anterograde vesicular trafficking rescued the growth defect of CT229/CpoS mutants and prevented host cell death (Rzomp, Moorhead, & Scidmore, ; Sixt et al, ; Weber et al, ).…”
Section: Impact Of Inc Proteins On Inclusion Stabilitysupporting
confidence: 62%
See 2 more Smart Citations
“…By targeted gene disruption of individual Inc proteins in Ctr , mutants of IncC, CT383, and CT229/CpoS exhibited a significant growth defect and premature inclusion lysis followed by host cell death. These results were further confirmed in mouse genital infection studies (Weber et al, ). Independent studies identified several Rab proteins as interaction partners of CT229/CpoS, and inhibition of host cell protein biosynthesis or anterograde vesicular trafficking rescued the growth defect of CT229/CpoS mutants and prevented host cell death (Rzomp, Moorhead, & Scidmore, ; Sixt et al, ; Weber et al, ).…”
Section: Impact Of Inc Proteins On Inclusion Stabilitysupporting
confidence: 62%
“…With the establishment of genetic tools for Chlamydia within the last years (Sixt et al, ), new insights in the role of Inc proteins during infection were obtained. Some Inc proteins specifically regulate interaction with host cell proteins and compartments (see above) whereas others are crucial for inclusion stability and evasion from cell‐autonomous host defence (Weber et al, ).…”
Section: The Chlamydia‐containing Vacuolementioning
confidence: 99%
See 1 more Smart Citation
“…Finally, we tested if IncV is required for the formation of ER-inclusion MCS by using an incV::bla mutant (43). We confirmed that the mutant harbors an intron insertion between nucleotide position 99 and 100 of the incV ORF, which is predicted to lead to the production of a truncated peptide containing the first 33 aa of IncV (Fig.…”
mentioning
confidence: 67%
“…However, it is unknown if Inc proteins can also act as structural components to bring and maintain the ER and the inclusion membrane in close apposition. C. trachomatis encodes more than 50 putative Incs and only some of them have known functions in C. trachomatis infection (24,28,(31)(32)(33)(34)(35)(36)(37)(38)(39)(40)(41)(42)(43). Recently, Mirrashidi et al (37) determined the Inc-human interactome from uninfected cells expressing C. trachomatis Inc proteins.…”
mentioning
confidence: 99%